Strategi Guru Pendidikan Agama Islam dalam Membina Akhlak Siswa pada Pembelajaran Tatap Muka Terbatas - Agus Hariyadi; Syahran Jailani; Minnah el-Widdah (Journal of Educational Research, 2023)
This study aims to describe the strategy of Islamic religious education teachers in fostering student morals during limited face-to-face learning. supporting and inhibiting factors in fostering student morals during limited face-to-face learning. The research method used is a qualitative approach. The results of the study show that the teacher's strategy in fostering student morals is very important to provide an overview, direction, goals, in controlling effective learning objectives. Teacher strategies that are often used include; blended learning, expository strategies, and teacher affective strategies that focus on fostering student attitudes such as habituation, exemplary, motivation, advice and gifts. The factors that support the teacher's strategy include; online activities such as webinars, online workshops and online training, blended learning strategies that make it easier for teachers to provide video material, pictures, quizzes and teaching materials, expository strategies that help teachers convey material in a limited time, and affective strategies can shape student morals by mature through understanding knowledge and habituation. While the inhibiting factors for the teacher's strategy include; decreased levels of teacher and student interaction, decreased student enthusiasm, and limited teacher ability in implementing the chosen strategy. Penelitian ini bertujuan untuk memaparkan strategi guru pendidikan agama Islam dalam membina akhlak siswa pada masa pembelajaran tatap muka terbatas. faktor pendukung dan penghambat dalam membina akhlak siswa pada masa pembelajaran tatap muka terbatas. Metode penelitian yang digunakan yaitu pendekatan kualilatif. Hasil penelitian menunjukkan bahwa strategi guru dalamÂ  membina akhlak siswa sangat penting untuk memberikan gambaran, arahan, tujuan, dalam mengontrol tujuan pembelajaran yang efektif. Strategi guru yang kerap digunakan antara lain; blended learning, strategi ekspositeri, dan strategi afektif guru yang berfokus pada membina sikap siswa seperti pembiasaan, keteladanan, motivasi, nasihat dan hadiah. Faktor-faktor yang mendukung strategi guru tersebut antara lain; kegiatan online seperti webinar, workshop online dan pelatihan online, strategi blended learning yang memudahkan guru dalam memberi materi vidio, gambar, quiz dan bahan ajar, strategi ekspositori yang membantu guru dalam menyampaikan materi dalam waktu yang terbatas, dan strategi afektif dapat membentuk akhlak siswa dengan matang melalui pemahaman ilmu dan pembiasaan. Sedangkan faktor penghambat strategi guru tersebut antara lain; menurunnya kadar interaksi guru dan siswa, semangat siswa yang menurun, dan keterbatasan kemampuan guru dalam melaksanakan strategi yang dipilih